Macromolecular crowding in Rhodobacter sphaeroides - Khoo, J (2020)
Macromolecular crowding is thought to have an important role in protein dynamics and molecular diffusion in bacteria. However, the dynamic and heterogeneous nature of the cytoplasm makes it challenging to study and test the significance of crowding in live cells. Previous studies have used diffusion coefficient of protein to estimate excluded volume in osmotically stressed or energy depleted cells, but the effects of crowding in unperturbed cells are unclear. The alphaproteobacterium Rhodobacter sphaeroides is a good candidate for studying crowding in vivo as it generates different number of intracytoplasmic membrane (ICM) vesicles occupying different amounts of cytoplasmic space under different light intensities. When grown heterotrophically under low light illumination, R. sphaeroides cells generate 3 to 4 times more vesicles than cells grown under high light, resulting in a dramatic change in the cellular architecture and increased crowding.